ORGANIZATIONAL AND PEDAGOGICAL FOUNDATIONS OF SELF-EDUCATIONAL ACTIVITY OF FUTURE PHARMACY MASTERS IN MASTERING MARKETING AND MANAGEMENT DISCIPLINES - Барджадзе, Руслана (SWorldJournal, 2025)
The article explores the organization of self-educational activities for pharmacy masters studying "Marketing and Management in Pharmacy" within an information educational environment. Conducted at Cherkasy Medical Academy with 45 master's students, the